RESTORATION OF ANGIOGENESIS BY ENALAPRIL IN DIABETIC HINDLIMB ISCHEMC RATS - Fallahzadeh, Ali Reza; Khazaei, Majid; Sharifi, Mohammad Reza (Biomedical papers, 2011)
Background: Angiotensin-converting enzyme inhibitors have different effects on the cardiovascular system. The aim of this study was to investigate the effect of enalapril on skeletal muscle angiogenesis in diabetic and diabetic hind limb ischemic rats.Methods: We studied 24 male diabetic rats (induced by streptozotocin, 55 mg/kg, ip) divided into four groups. Groups 1 and 2 were diabetic sham (surgical procedure without femoral artery ligation). Groups 3 and 4 were diabetic animals subjected to induced hind limb ischemia. Groups 2 and 4 received enalapril (15 mg/kg/day, i.p) and groups 1 and 3 received an equal volume of saline. After 21 days, capillary density, capillary to fiber (cap/fib) ratio and serum concentrations of nitric oxide (NO), Vascular Endothelial Growth Factor (VEGF) and soluble VEGF Receptor-1 (sVEGF-R1) were evaluated.Results: Enalapril significantly increased serum NO and VEGF concentrations and reduced serum sVEGF-R1 concentrations in diabetic sham and hind limb ischemic rats (p<0.05). Administration of enalapril significantly increased capillary density and cap/fib ratio in diabetic sham and hind limb ischemic animals compared with nontreated groups (p<0.05).Conclusions: Enalapril restores skeletal muscle angiogenesis in diabetic hind limb ischemia and can be considered for the prevention and treatment of peripheral artery disease in diabetic subjects.
Keywords: Diabetes/Hind limb ischemia/Capillary density/Enalapril/Rat